The comprehension of figurative language by Afrikaans-speaking children with and without specific language impairment and by child second language speakers of Afrikaans - Van der Merwe, Kristin Catherine (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2008.